2021
DOI: 10.1002/oby.23185
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of binge eating, loss of control eating, and weight loss in children and adolescents

Abstract: Pediatric obesity is a global health concern. Rates of obesity in pediatric populations remain high in developed countries such as the United States and Canada, with prevalence rates of 18.5% and 13.1%, respectively (1). This is of particular importance because of the association of pediatric obesity with metabolic syndrome, inflammation, and a variety of other comorbidities (2). Current weightmanagement treatments for pediatric patients include behavioral therapy, pharmacotherapy, and bariatric surgery (3). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 80 publications
(142 reference statements)
1
20
0
2
Order By: Relevance
“…Indeed, in their meta-analysis, He et al indicated that BED or LOC eating was prevalent (i.e., slightly over a quarter of the population) among children and adolescents that were overweight or obese [ 37 ]. These results were confirmed by He et al, who estimated the prevalence of binge eating and LOC eating to be 26.3% in children and adolescents affected by being overweight or obese, and recently verified by Moustafa et al, who estimated rates of LOC eating episodes at about 31.2% in overweight youth [ 36 ]. Both BED and LOC eating are more prevalent in children and adolescents that are overweight compared to peers with normal weight [ 34 ].…”
Section: Binge Eating Disorder In Adolescents With Obesitysupporting
confidence: 60%
See 4 more Smart Citations
“…Indeed, in their meta-analysis, He et al indicated that BED or LOC eating was prevalent (i.e., slightly over a quarter of the population) among children and adolescents that were overweight or obese [ 37 ]. These results were confirmed by He et al, who estimated the prevalence of binge eating and LOC eating to be 26.3% in children and adolescents affected by being overweight or obese, and recently verified by Moustafa et al, who estimated rates of LOC eating episodes at about 31.2% in overweight youth [ 36 ]. Both BED and LOC eating are more prevalent in children and adolescents that are overweight compared to peers with normal weight [ 34 ].…”
Section: Binge Eating Disorder In Adolescents With Obesitysupporting
confidence: 60%
“…The term LOC eating is used to describe episodes with LOC, where the amount eaten is either not defined or not objectively large [ 34 ]. This term is extremely useful in children and adolescents, as it is challenging to define “a large amount of food” for them when considering possibilities such as increases in calories related to growth spurts [ 36 ]. The LOC eating episodes can be further subdivided into subjective binge episodes (SBEs), in which the individual experiences a loss of control and does not consume an objectively large amount of food, and objective binge episodes (OBEs), in which the patient experiences both a loss of control and consumes an objectively large amount of food [ 36 ].…”
Section: Binge Eating Disorder In Adolescents With Obesitymentioning
confidence: 99%
See 3 more Smart Citations